A NEW SECURE VIDEO TRANSMISSION TECHNIQUE USING NEARLY REVERSIBLE COLOR TRANSFORMATIONS ON FRAGMENTED MOSAIC FRAMES - Xavier, Jinu; Sunny, Leya Elizabeth (IJRDO -Journal of Computer Science Engineering, 2015)
A new secure video transmission technique is proposed which transforms the frames of the secret video into a so called secret fragment visible mosaic frames of the same size. The mosaic frame which looks similar to an arbitrarily selected target video frame and may be used as a camouflage of the secret frame, is yielded by dividing the secret frame into fragments and transforming their color characteristics to be those of the corresponding blocks of the target frame. Skillful techniques are designed to conduct the color transformation process and also suitable rotations of the mosaic frame is done so that the secret image may be recovered nearly losslessly and target image looks like original one. A scheme of handling the overflows/underflows in the converted pixels color values by recording the color differences in the untransformed color space is also proposed. Moreover the embedding details, rotation details and color transformation details will be shuffled with a pseudo random number using a key value in such a way that only the intended recipient who has the key will be able to retrieve back the secret data from the cover video without any distortion to both. This can be considered as a lossless data hiding method and a secured one.